2019
DOI: 10.1073/pnas.1916318116
|View full text |Cite
|
Sign up to set email alerts
|

N , N ′-Diacetyl- p -phenylenediamine restores microglial phagocytosis and improves cognitive defects in Alzheimer’s disease transgenic mice

Abstract: As a central feature of neuroinflammation, microglial dysfunction has been increasingly considered a causative factor of neurodegeneration implicating an intertwined pathology with amyloidogenic proteins. Herein, we report the smallest synthetic molecule (N,N′-diacetyl-p-phenylenediamine [DAPPD]), simply composed of a benzene ring with 2 acetamide groups at the para position, known to date as a chemical reagent that is able to promote the phagocytic aptitude of microglia and subsequently ameliorate cognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…The process is a proinflammatory form of programmed cell death termed as pyroptosis [85][86][87]. Accumulating evidence suggests that the NLRP3 inflammasome plays an important role in inflammation in the central nervous system [88,89] and cognitive deficits [90]. Moreover, a previous study demonstrated that the NLRP3 inflammasome could be regulated by ROS and mitophagy in the reverse direction [13].…”
mentioning
confidence: 99%
“…The process is a proinflammatory form of programmed cell death termed as pyroptosis [85][86][87]. Accumulating evidence suggests that the NLRP3 inflammasome plays an important role in inflammation in the central nervous system [88,89] and cognitive deficits [90]. Moreover, a previous study demonstrated that the NLRP3 inflammasome could be regulated by ROS and mitophagy in the reverse direction [13].…”
mentioning
confidence: 99%
“…The availability of the Ephx2 conditional allele(38) allows deciphering the cell-type specific effect and central-peripheral interactions. Additionally, the NLRP3 inflammasome activation has been implicated in producing harmful chronic inflammatory reactions and impairing microglial Aβ clearance and cognitive function in AD(8,44,45). Indeed, we found that Nlrp3 and Casp1 were both upregulated in Tg mice and downregulated by TPPU treatment.…”
mentioning
confidence: 63%
“…These findings and new insights lead to the interesting proposal of the feedback hypothesis instead of the prevailing amyloid cascade hypothesis of AD. There is increasing evidence to suggest that breaking such positive feedback loops is a promising approach to intervene in the pathogenesis and progression of AD [ 212 ]. Currently, there are no effective treatments, or a substantial unmet clinical need, for many debilitating diseases or conditions of which the TRPM2 channel plays an important part in the pathogenesis and progression.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%